Sutton Hoo and Syria: the Anglo-Saxons who served in the Byzantine Army? - Gittos, H (Oxford University Press, 2025)
The Sutton Hoo ship burial is one of the most famous examples of a group of lavishly furnished graves of the late sixth and early seventh centuries in south-east England. The discovery in 2003 of another, at Prittlewell (in Southend, Essex), and its publication in 2019, has brought our knowledge of them into sharper focus. One of the characteristics of these burials is that they tend to contain objects that were made in the eastern Mediterranean which were current, rather than old, when buried, and were of very unusual types. This article argues that they were acquired by men who were recruited into the Byzantine army in 575 to serve on the eastern front against the Sasanians. Those who returned brought back with them metalwork and other items which were current, and distinctive, and not the kinds of things that were part of normal trading networks. This opens up a startlingly new view onto early medieval British history.